Modeling of Tunnel Advanced Geological Prediction and Forward Simulation of Seismic Wave Propagation - Jia, Shengyuan (International Journal of Natural Resources and Environmental Studies, 2025)
With the rapid development of transportation infrastructure in China, an increasing number of railway, highway, and urban rail transit projects have emerged like bamboo shoots after rain. Nevertheless, many tunnel projects still face significant challenges during construction, which constrain overall transportation development. In tunnel engineering, adverse geological formations such as fractured zones, karst caves, and faults are frequently encountered. Failure to detect these hazardous geological bodies in a timely manner and implement appropriate construction measures may not only delay project progress but also pose serious threats to the safety of construction personnel. Tunnel advanced geological prediction technology, employing the seismic reflection method, provides accurate characterization of geological conditions near the tunnel face. As an approach for advanced detection, wavefield forward simulation offers convenience and precision. However, reliable forward simulation requires accurate geological models. Therefore, this study focuses on analyzing the characteristics of various geological models and develops a programmatic approach to generate these models to meet the requirements of forward simulation. Finally, the wavefield characteristics are comparatively analyzed based on the forward simulation results derived from the geological models.